Reformasi Administrasi dan Desentralisasi Pada Masa Dinasti Ummayah di Damaskus (670-750 M) - Ibrahim Rantau, Muhammad; Permana Putra, Heru; Suwarno, Peter (Universitas Islam Negeri Raden Intan Lampung, 2025)
Research on classical Islamic administrative systems tends to emphasize the centralization of caliphal power, yet insufficiently explores the complexity of center-periphery relations in governmental practice. This article analyzes the paradox between political centralization and administrative decentralization during the Umayyad Dynasty in Damascus (670-750 CE) to address gaps in Islamic political history literature. This qualitative research employs a library research approach. Although the Umayyad Dynasty's political system was characterized by absolute monarchy with power centralized in the caliph, governmental administrative practices demonstrated significant administrative decentralization. Provincial governments were granted autonomy to independently manage conquered territories as a response to the geographical and administrative complexities of the vast empire. These findings challenge conventional views regarding the complete centralization of Umayyad governance and contribute to understanding the evolution of Islamic protobureaucracy. This research has theoretical implications for historical public administration and contemporary relevance for discussions of center-periphery relations in modern Muslim world governance.